Genome-Wide Association Study of Maize Aboveground Dry Matter Accumulation at Seedling Stage - Lu, Xianju; Wang, Jinglu; Wang, Yongjian; Wen, Weiliang; Zhang, Ying; Du, Jianjun; Zhao, Yanxin; Guo, Xinyu (Frontiers in Genetics, 2021)
Dry matter accumulation and partitioning during the early phases of development could significantly affect crop growth and productivity. In this study, the aboveground dry matter (DM), the DM of different organs, and partition coefficients of a maize association mapping panel of 412 inbred lines were evaluated at the third and sixth leaf stages (V3 and V6). Further, the properties of these phenotypic traits were analyzed. Genome-wide association studies (GWAS) were conducted on the total aboveground biomass and the DM of different organs. Analysis of GWAS results identified a total of 1103 unique candidate genes annotated by 678 significant SNPs (P-value<1.28e-6). And 224 genes annotated by SNPs that at the top five of each GWAS method and detected by multiple GWAS methods were regarded as of high reliability. Pathway enrichment analysis was also performed to explore the biological significance and functions of these candidate genes. Several biological pathways related to the regulation of seed growth, gibberellin mediated signalling pathway, and long-day photoperiodism were enriched. The results of our study could provide new perspectives on breeding high-yielding maize varieties.